Strategies to Improve the Biosynthesis of β-Lactam Antibiotics by Penicillin G Acylase: Progress and Prospects - Pan, Xin; Xu, Lei; Li, Yaru; Wu, Sihua; Wu, Yong; Wei, Wenping (Frontiers in Bioengineering and Biotechnology, 2022)
β-lactam antibiotics are widely used anti-infection drugs that are traditionally synthesized via chemical process. In recent years, with the growing demand for green alternatives, scientists have turned to enzymatic synthesis. Penicillin G acylase (PGA) is the second most commercially used enzyme worldwide with both hydrolytic and synthetic activity towards antibiotics, which has been used to manufacture the key antibiotic nucleus on an industrial level. However, the large-scale application of PGA-catalyzed antibiotics biosynthesis is still in the experimental stage because of some key limitations, such as low substrate concentration, unsatisfactory yield, and lack of superior biocatalysts. This paper systematically reviews the strategies adopted to improve the biosynthesis of β-lactam antibiotics by adjusting the enzymatic property and manipulating the reaction system in recent 20 years, including mining of enzymes, protein engineering, solvent engineering, in situ product removal, and one-pot reaction cascade. These advances will provide important guidelines for the future use of enzymatic synthesis in the industrial production of β-lactam antibiotics.